TEACHING LETTER WRITING TO LARGE CLASSES - lalu merdi (ISSN)
Teaching letter writing has been regarded as a difficult task in most of circumstances where English is taught as a foreign language. The task is made more difficult when the class is a large class, especially when it comes to the correcting and marking of the students’ paper. In an attempt to minimize the problems of doing the job, many experts have proposed a variety of approaches but none seems to be the right solution. This paper is trying to present an empirical technique of teaching letter writing at Brawijaya University where the average number of the students taking the course is relatively large. And the most plausible technique that can be practiced to relieve the teacher’s burden is the peer correcting and/or peer marking.